2022
DOI: 10.1515/bmc-2022-0026
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human papillomavirus in pregnant women in Burkina Faso

Abstract: Introduction Genital human papillomavirus (HPV) infection is widespread among sexually active individuals. Several factors may contribute to increased risk of infection in pregnant women. The objective of this study was to determine the high-risk (HR-HPV) and low-risk (LR-HPV) oncogenic HPV genotypes among pregnant women in Ouagadougou. Methodology In this study, 100 endocervical samples were collected using a sterile swab on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…This could be explained by the much larger sample size (1321) and could mean that viral hepatitis B and C do not play a role in the occurrence or persistence of HPV infection. The prevalence found in our study was higher than that found among pregnant women (23%) in Burkina Faso with the same sample size as ours [18]. The Brazilian study found 20/103 HPV-positive individuals, with the 2 hepatitis B/C coinfected individuals being HPV-and HIV-positive [28].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…This could be explained by the much larger sample size (1321) and could mean that viral hepatitis B and C do not play a role in the occurrence or persistence of HPV infection. The prevalence found in our study was higher than that found among pregnant women (23%) in Burkina Faso with the same sample size as ours [18]. The Brazilian study found 20/103 HPV-positive individuals, with the 2 hepatitis B/C coinfected individuals being HPV-and HIV-positive [28].…”
Section: Discussioncontrasting
confidence: 59%
“…HPV 11 was found in only one patient. In pregnant women, [18] found HPV 6, 62/81 and 44/55 with respective percentages of 3.45%, 6.89% but HPV 11was not found. We found 53.57% multiple infections in this study.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In Burkina Faso, the prevalence of HPV infection is high (37.09%) among sexually active women [16]. Studies on HPV have mainly focused on adults [17]- [24]. No data are available on mother-to-child transmission of HPV in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%